Partisanship and Fiscal Policy in Federal Unions: Evidence from US States - Gerald Carlino; Thorsten Drautzburg; Robert Inman; Nicholas Zarra (ZBW - Leibniz Information Centre for Economics, 2020)
In federal countries, such as the U.S., the fiscal authority consists not of one, but many governments, with state governments accounting for a sizable share of expenditures. We analyze how state partisanship of politicians affects state fiscal policy and quantify the possible macroeconomic consequences for federal fiscal policy. First, using data from close elections, we find strong partisanship effects in the marginal propensity to spend federal transfers, the so-called y-paper effect: Republican governors spend less. Second, this partisan difference has increased over time and is correlated with the political polarization of federal policymakers. Third, we calibrate a two-agent New Keynesian model of Republican and Democratic states in an open economy monetary union, calibrated to deliver defense spending multipliers as in the literature. Lowering back partisan differences to the less-polarized pre-Reagan era would increase the transfer multiplier by about 30 cents per dollar, and variation in governor's partisan composition similarly lead to variation in the multiplier of around to 20 cents. Fourth, we provide direct support for the structural model's partisan predictions using local-projection methods.
Keywords: C24; E62; F45; H72; H77; 330; partisanship; flypaper effect; intergovernmental transfers; fiscal multiplier; monetary union; regression discontinuity